Moderate consumption of wine, through both its phenolic compounds and alcohol content, promotes hydroxytyrosol endogenous generation in humans. A randomized controlled trial. Issue 6 (27th April 2015) - Pérez‐Mañá, Clara; Farré, Magí; Rodríguez‐Morató, Jose; Papaseit, Esther; Pujadas, Mitona; Fitó, Montserrat; Robledo, Patricia; Covas, Maria‐Isabel; Cheynier, Véronique; Meudec, Emmanuelle; Escudier, Jean‐Louis; de la Torre, Rafael
<x xml:space="preserve">Abstract</x> In humans, urinary hydroxytyrosol (OHTyr) concentrations have been associated to alcohol and wine consumption. To explore the role of wine components on promoting an endogenous OHTyr generation we performed a cross‐over, double‐blind, randomized controlled clinical trial (n = 28 healthy volunteers). Ethanol (wine and vodka), dealcoholized wine, and placebo were administered. Alcohol, dealcoholized wine, and particularly wine promoted a de novo OHTyr generation in vivo in humans. Potential OHTyr precursors (tyrosine, tyrosol, tyramine) were investigated in rats. Tyrosol was metabolized to OHTyr. Collating both studies, it is postulated that an increased Tyr bioavailability, a shift to a reductive pathway in dopamine and tyramine oxidative metabolism, and the biotransformation of Tyr to OHTyr were mechanisms involved in the OHTyr endogenous generation.